(untitled) (Semiárida, 2020)
The objective of the present study was to obtain a precise evaluation of the frost regime in the eastern part of La Pampa Province. Oaily data set of minimum temperatures (1,50 and 0,05 m above ground level) at General Pico, Anguil, General Acha and Bordenave were used for the period from 1973 to 1998. Means and variability for medium date of first and last frost were calculated and used to construct the respective maps. Determination of extreme frost dates, medium frost free and frost period, winter harshness and danger indexes was effected. A marked increase in the bharshness of the agroclimatic frost regime was observed in a Northeast to Southwest direction. The indexes of danger (ICK) of autumn and spring frost marked a significant increase in the risk level in the south-western direction of the region.